Understanding the aroma diversity of Dancong tea (Camellia sinensis) from the floral and honey odors: Relationship between volatile compounds and sensory characteristics by chemometrics. (October 2022) - Chen, Wei; Hu, Die; Miao, Aiqing; Qiu, Guangjun; Qiao, Xiaoyan; Xia, Hongling; Ma, Chengying
Abstract: Dancong is a Chinese oolong tea famous for its aroma diversity. However, this diversity in characteristic is challenging to be clarified in either sensory or chemical aspects. In this study, the aromas from Dancong teas were characterized based on the typical odors of "floral" and "honey". The volatile compounds underlying the odors were investigated through chemometrics. Seventy Dancong teas of various categories were collected to approximate the diversity in aroma. According to the sensory evaluation, the floral or honey odor was detected in every sample. For volatile characterization, 57 compounds were identified by gas chromatography-mass spectrometry (GC-MS) coupled with headspace-solid phase microextraction (HS-SPME) across samples. The difference in floral and honey odors was related to volatile variation among the teas, as both the odor-based classification and the volatile-based unsupervised learning analyses yielded consistent sample clustering patterns. Nine volatiles were identified as putative markers for the odor difference, where indole, ( E )-nerolidol, 2-phenylacetonitrile, and γ-caprolactone accounted for the floral odor predominance, while hexyl 2-methylbutanoate, ( Z )-3-hexenyl pentanoate, ( Z )-linalool oxide (pyranoid), ( E )-linalool oxide (furanoid), and ( Z )-linalool oxide (furanoid) contributed to the honey odor perception. These results point to a volatile-endorsed categorization framework based on the floral and honey odors that can assist in Dancong aroma quality control. Graphical abstract: Image 1 Highlights: Aroma diversity among Dancong can be characterized by floral and honey odors. Floral and honey odor difference from Dancong was rooted in volatile variation. Four markers such as indole and ( E )-nerolidol linked to floral odor. Five markers including fatty acid esters and linalool oxides linked to honey odor.